Assessment on subjective sustainable well-being for central region of Malaysia - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor; Abdullah, Alias (American Scientific Publishers, 2017)
Sustainable well-being results from a well-being that sustained at another’s expense. That is the well-being achieved from supportive interaction system and sourced from the well-being of others. Thorough investigations suggested that subjective sustainable well-being is achieved through interdependencies between human and other humans and between human and the environment. By analyzing the levels of interdependencies, this paper emphasizes the significant differences between the urban, suburban and rural community in attaining sustainable well-being in the most urbanized and populated regions of Malaysia.